Prevalence, awareness, treatment and control of high blood pressure in a cohort in Northern Andean Peru - Giuliana Sanchez-Samaniego; Stella Maria Hartinger; Daniel Mäusezahl; Jan Hattendorf; Günther Fink; Nicole Probst-Hensch (Taylor & Francis Group, 2023)
Background Gaps exist along the high blood pressure (HBP) diagnosis-treatment-control pathway in high, low and middle-income countries. Objective To determine the prevalence of HBP and to describe the levels of awareness, control and treatment of HBP in the rural Peruvian Andes. Methods This cross-sectional study is embedded into a multigenerational cohort. We analysed data of all adult participants aged ≥ 30 years (n = 2752) who answered a baseline health and lifestyle questionnaire and underwent a physical examination, which included three blood pressure readings. HBP was defined as measured systolic or diastolic blood pressure (BP) ≥140 and/or 90 mm Hg and/or self-reported physician-diagnosed hypertension and/or self-reported antihypertensive intake. The determinants of the prevalence of HBP, unawareness of HBP and uncontrolled HBP were assessed using mixed-effect logistic regressions. Results HBP was present in 18.9% of the participants. Of those with measured HBP, 72.2% were unaware of their HBP. Among those with a diagnosed or medically treated hypertension, 58.4% had uncontrolled HBP. The prevalence of HBP was higher in women (OR: 1.12, CI: 1.02-1.24), increased with age (OR: 1.01, CI: 1.01-1.01) and the presence of family history of hypertension (OR: 1.15, CI: 1.08-1.24), and decreased with healthier lifestyle score (OR: 0.93, CI: 0.91-0.95). Unawareness of HBP was lower among women (OR: 0.56, CI: 0.38-0.83), higher among participants living over 3000 m Above Sea Level (OR: 1.15, CI: 1.03-1.27) and decreased with age (OR: 0.99, CI: 0.98-0.99). Conclusions Unawareness of HBP was high, few HTN patients received treatment and BP remained high in the presence of antihypertensive treatment.